EFFICIENT ARCHITECTURAL APPROACHES FOR BUSINESS INTELLIGENCE SYSTEMS (Uzbekistan Open Conference, 2025)
This paper analyzes the architecture of a problem-oriented Business Intelligence (BI) system and its core components. The study highlights that the efficiency of BI solutions depends on proper data flow management, metadata layer implementation, ETL processes, and the introduction of an Operational Data Store (ODS). Comparative analysis of QlikView, SAP BI, and Microsoft Power BI architectures was conducted to identify their advantages and limitations. The findings demonstrate that integrating a metadata layer, ensuring data quality and security, and optimizing user access and workload balance significantly improve BI system performance. The paper concludes with a proposed problemoriented BI architecture model structured by data quality, security, user management, reporting, and load balancing levels.